Human diaphragm atrophy in amyotrophic lateral sclerosis is not predicted by routine respiratory measures. Issue 2 (14th February 2019) - Guimarães-Costa, Raquel; Similowski, Thomas; Rivals, Isabelle; Morélot-Panzini, Capucine; Nierat, Marie-Cécile; Bui, Mai Thao; Akbar, David; Straus, Christian; Romero, Norma Beatriz; Michel, Patrick Pierre; Menegaux, Fabrice; Salachas, François; et al.
Amyotrophic lateral sclerosis (ALS) patients show progressive respiratory muscle weakness leading to death from respiratory failure. However, there are no data on diaphragm histological changes in ALS patients and how they correlate with routine respiratory measurements. We collected 39 diaphragm biopsies concomitantly with laparoscopic insertion of intradiaphragmatic electrodes during a randomised controlled trial evaluating early diaphragm pacing in ALS (https://clinicaltrials.gov ; NCT01583088). Myofibre type, size and distribution were evaluated by immunofluorescence microscopy and correlated with spirometry, respiratory muscle strength and phrenic nerve conduction parameters. The relationship between these variables and diaphragm atrophy was assessed using multivariate regression models. All patients exhibited significant slow- and fast-twitch diaphragmatic atrophy. Vital capacity (VC), maximal inspiratory pressure, sniff nasal inspiratory pressure (SNIP) and twitch transdiaphragmatic pressure did not correlate with the severity of diaphragm atrophy. Inspiratory capacity (IC) correlated modestly with slow-twitch myofibre atrophy. Supine fall in VC correlated weakly with fast-twitch myofibre atrophy. Multivariate analysis showed that IC, SNIP and functional residual capacity were independent predictors of slow-twitch diaphragmatic atrophy, but not fast-twitch atrophy. Routine respiratory tests are poor predictors of diaphragm structural changes. Improved detection of diaphragm atrophy is essential for clinical practice and for management of trials specifically targeting diaphragm muscle function. Vital capacity and other widely used respiratory measures are poor predictors of diaphragmatic atrophy. Vital capacity should not be used as the sole selection criteria in clinical trials targeting diaphragm mass or function http://ow.ly/7GEg30mIpCK